SEJARAH PERKEMBANGAN ILMU FALAK DALAM PERADABAN INDIA DAN KETERKAITANNYA DENGAN ISLAM - reza akbar (Islam Futura, 2017)
Although it is acknowledged that Islamic astronomy developed very rapidly during the Abbasid period (750-1258 AD), it should be noted that before the advancement of astronomy of the Islamic world, Muslim scholars of the time were very incentive to translate astronomical books from other nations, one of them was from India. There were at least two factors that led to the emergence and development of astronomical science in pre-Islamic Indian civilization. The first, the teachings of Hinduism that made the sun as the ruler and source of life. The second, the influence of civilization from other nations such as Egypt, Persia, and Greece. In pre-Islamic times, there were a number of names of historical figures of Indian astronomy namely Lagadha, Yajnavalkya (800-900 BC), Aitareya Brahmana (about 900-800 BC), Aryabhata (476-550 AD), Varahamihira (499-587 AD) Brahmagupta (598-668 AD), Bhaskara II (1114-1185 AD), and Nilakantha Somayaji (1444-1544 AD). While in Islam, there was a number of names namely Mulla Farid, Mulla Chand, Mulla Tayyib, Mulla Mahmud Jaunpuri (1606-1651 AD), Ghulam Hussain Jaunpuri (1790-1862 AD) and others. The results of civilization of Indian astronomy is clearly visible with the ancient astronomical texts, the concept of the universe, the Hindu calendar, observatory, zij (astronomical tables), and astronomical tools such as gnomon, Yasti Yantra, Ghati Yantra, astrolabe, and others.